“The Extent Of Commitment To The Principles Of Transparency And Confidentiality In Commercial Arbitration” “A Study In The Saudi And Comparative System” - Abdelgawad, Dr. Mahmoud Abdelgawad Abdelhadi (The journal of contemporary issues in business and government, 2021)
Confidentiality in arbitration is its unique and exclusive advantage .It is also considered one of the factors that attract foreign investments whose disputes are often required to be resolved through arbitration. However, the international investments in which the state is a party, confidentiality does not have the same degree of commitment compared to the commitment to transparency in investment disputes. In international investment treaties, confidentiality should be excluded as foreign investments, in which the state is often a party, are always associated with the public interest of the host state, and is subject to the influences of public policy and public opinion, and hence transparency is an inevitable requirement. Adopting transparency to the required extent in resolving disputes through arbitration and disclosure of its results and the progress of its procedures inevitably leads to the stability of capital and attracting more capital to the country incubating foreign investments, as long as such transparency is positive and fair. However, transparency and absolute disclosure cannot be adopted regarding the disputes raised in the field of commercial arbitration. As the reputation of the litigant parties and their financial positions are considerably and directly affected by what may be reported in terms of news. This may lead to tremendous economic losses and the reluctance to invest in such countries, and to other further negative consequences resulting from the absolute disclosure and announcement of everything that is raised thereof. Accepting or rejecting transparency against confidentiality of arbitration, especially in the field of international investment, is not a recent disagreement, but rather an inherent disagreement between the two principles, confidentiality and transparency.